Early protoplast culture and partial regeneration in Cannabis sativa: gene expression dynamics of proliferation and stress response - Král, Daniel; Šenkyřík, Josef Baltazar; Ondřej, Vladan (Frontiers in Plant Science, 2025)
Cannabis sativa L. is a plant of significant interest due to its high content of biologically active compounds, durable fibers, and bioeconomic potential. Despite recent progress in protoplast isolation, complete plant regeneration from cannabis protoplasts remains unachieved, highlighting gaps in protoplast-to-plant systems. This study reports the second successful establishment and partial regeneration of cannabis protoplast cultures, and investigates their molecular dynamics, marking a significant step forward. We demonstrated that the age of donor material is critical for the protoplast isolation, with the optimal source being 1–2-week-old leaves from in vitro-grown seedlings. Cultivation in a modified medium developed for Arabidopsis thaliana supported initial cell divisions and microcallus formation. Transcriptomic analyses of cell proliferation and stress response markers indicate that the cultured protoplasts were viable, re-entered the cell cycle, and exhibited oxidative and abiotic stress resilience. These findings enhance our understanding of cannabis cell biology and lay the groundwork for a protoplast-based regeneration system, paving the way for advanced applications in biotechnology.